2007
DOI: 10.1080/10407780701634458
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a Short-Pulse Laser of a Gaussian Temporal Profile with an Inhomogeneous Medium

Abstract: Transport of a short-pulse laser in an inhomogeneous planar participating medium is investigated. The pulse is a Gaussian function in time. Discrete as well as continuous variations in the scattering albedo across the layers are considered to be the cause of inhomogeneties in the absorbing-scattering medium. Optical depths of different layers too are considered different. The finite volume method is used to analyze the problem. Transmittance and reflectance signals are studied for different situations. Charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Most of them focused their analyses on a simple one-dimensional (1-D) planar geometry [14,18,22,[26][27][28][29][32][33][34]. Some have also solved problems in two-dimensional (2-D) [17,20,21] and three-dimensional (3-D) Cartesian geometries [24,30].…”
Section: Introductionmentioning
confidence: 99%
“…Most of them focused their analyses on a simple one-dimensional (1-D) planar geometry [14,18,22,[26][27][28][29][32][33][34]. Some have also solved problems in two-dimensional (2-D) [17,20,21] and three-dimensional (3-D) Cartesian geometries [24,30].…”
Section: Introductionmentioning
confidence: 99%
“…1-D planar medium [11][12][13][14][15][16][17][18][19][20][21] as well as multi-dimensional [22][23][24][25][26][27][28][29][30] geometries, have been considered in the analysis. Cases of the incident radiation source having step [16,17,20,23] as well as Gaussian temporal profiles [11][12][13][14][15]18,19,21,22,[24][25][26][27][28][29][30] have been considered. Study has also been reported with diffuse as well as collimated radiation sources.…”
Section: Introductionmentioning
confidence: 99%
“…Study has also been reported with diffuse as well as collimated radiation sources. Different researchers have done the analysis using different numerical radiative transfer methods, viz., differential approximation [13], discrete ordinates method (DOM) [11,16,20,22,27,29], discrete transfer method (DTM) [16,18], finite element method [15], Monte Carlo method [24,26], radiation element method [14] and the finite volume method (FVM) [16,17,19,21,23].…”
Section: Introductionmentioning
confidence: 99%
“…The problem of a transient radiative transfer has been addressed in numerous investigations, especially in the last decade [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. However, only few of these studies were concerned with biomedical applications.…”
Section: Introductionmentioning
confidence: 99%